Tiny Bird, Huge Mystery - The Possibly Extinct Hooded Seedeater (Sporophila melanops) Is a Capuchino with a Melanistic Cap - Areta, Juan Ignacio (2016)
Known with certainty solely from a unique male specimen collected in central Brazil in the first quarter of the 19th century, the Critically Endangered (Possibly Extinct) Hooded Seedeater Sporophila melanops has been one of the great enigmas of Neotropical ornithology, arguably the only one of a host of long-lost species from Brazil to remain obstinately undiscovered. We reanalysed the morphology of the type specimen, as well as a female specimen postulated to represent the same taxon, and sequenced mitochondrial DNA (COI and Cyt-b) from both individuals. Furthermore, we visited the type locality, at the border between Goiás and Mato Grosso, and its environs on multiple occasions at different seasons, searching for birds with similar morphology to the type, without success. Novel genetic and morphological evidence clearly demonstrates that the type of S. melanops is not closely related to Yellow-bellied Seedeater S. nigricollis, as has been frequently postulated in the literature, but is in fact a representative of one of the so-called capuchinos, a clade of attractively plumaged seedeaters that breed mostly in the Southern Cone of South America. Our morphological analysis indicates that S. melanops has a hitherto unreported dark-coffee throat and that it is probably a Dark-throated Seedeater S. ruficollis collected within its wintering range, acquiring breeding plumage and showing melanism on the cap feathers. Alternatively, it may be a melanistic-capped individual of a local population of seedeaters known to breed in the Esteros del Iberá, Corrientes, Argentina, to which the name S. ruficollis might be applicable, whilst the name S. plumbeiceps might be available for what is currently known as S. ruficollis. A hybrid origin for S. melanops cannot be ruled out from the available data, but seems unlikely. The purported female specimen of S. melanops pertains either to S. nigricollis or to Double-collared Seedeater S. caerulescens based on genetic and morphological data, and thus cannot be a female of S. melanops. We conclude that Sporophila melanops is not typical of any natural population of seedeaters, appears to have been collected far from its breeding grounds while overwintering in central Brazil, and should not be afforded any conservation status.